Usability testing of academic library websites of selected institutions of higher learning in Diliman, Quezon City - Legaspi, Gian Carlo C.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study aimed to test the usability of the selected college and universities' library websites through the following questions: (1) How easy to use is the academic library website? (2) How efficient is the academic library website? (3) What are the problems that interfere with the navigation through the website? (4) How satisfied are the users in their experience in the website? (5) What are the ways to improve the library website to fit the user's needs? To answer these questions, three academic institutions were chosen namely: Ateneo de Manila University, Miriam College and the University of the Philippines as the main source of data to be studied because they are the academic institutions included in the area Diliman, Quezon City which is considered as one of the academic centers in Metro Manila and they were the only higher education institutions around the Diliman, Quezon City who have an academic library websites.
The study used a descriptive survey to evaluate and assess the library websites' resources and services. The survey questionnaires used were designed to test the usability of the library website. A total of 21 respondents were surveyed, seven from each academic institution. The data collected were tabulated and analyzed using frequency counts and percentage. The study revealed that librarians have a big responsibility in the usability of a library website. A simpler approach to the layout of the website increases the usability of the website. The study also revealed that Internet has been a part of everyday lives of the respondents. Thus, libraries should keep this in mind when choosing and designing the icons, layout and terminologies in the library website in order to take advantage of the internet to provide a much wider service to its users. This also shows that libraries are still needed even in the World Wide Web. It is recommended to provide orientation to students on the interface of the website, on what materials/information can be obtained from the library website. The students will become familiar with the library website and as a result will obtain faster retrieval of information. Future usability tests and a more detailed approach are also recommended to further test the usability of the library websites.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Ateneo de Manila University; Miriam College; University of the Philippines (Diliman).; Library web sites -- Philippines -- Quezon City